Influência de intervenção didática sobre estímulos ostensivos de um filme publicitário em textos escritos por alunos do 9º ano do ensino fundamental: estudo de caso com base na teoria da relevância - Bonifácio, Ligiane Pessoa dos Santos (2011)
Based on Relevance Theory, this case study analyzed the influence of a didactic intervention on ostensive stimuli of the advertising film Bar da Boa 1 - "Introdução", in post-test compositions written in classroom by ninth grade students of Arthur Engrácio da Silva School of Manaus, Amazonas, in November 2010. This research was consisted of three stages: first of all, students composed their texts, after watching the advertising film; secondly, there was a didactic intervention about ostensive stimuli of the film and their associated messages; and finally, the students composed another text. Results showed that, due to the didactic intervention, students explored and deepened in the post-test compositions utterances of the ostensive stimuli of the film that were not considered in the pre-test composition. Based on the instrument of data analysis, and on Rauen (2010) methodology, we verified that the utterances of the second compositions demonstrated some marks of students’ higher comprehension about the ostensive elements of the film, going from a simple syncretic description present in the first compositions, to the developed arguments influenced by the didactic intervention in the second compositions. In addition, the post-test compositions showed some influence of previously stimulated cognitive environments as well as the occurrence of new information.